2006
DOI: 10.1097/01.pep.0000200952.63544.16
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Bone Mineral Density in Adolescent Female Swimmers, Soccer Players, and Weight Lifters

Abstract: Participation in sports such as soccer or weight lifting with significant skeletal loading may enhance BMD in adolescent females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 18 publications
4
36
1
3
Order By: Relevance
“…13 Previous studies based on this phenomenon reported that soccer players showed significantly higher BMD than swimmers who had no weight bearing, but there was no difference between swimmers and weightlifters after the analysis of BMD in soccer players, swimmers, and weight lifters. 11 These results are not consistent as one study showed higher bone density in weight lifters than runners, 19 while another study reported that weight lifters showed significantly higher bone density than non-athletes. 20 In summary, athletes show higher bone density than non-athletes, and it is assumed that the reason for the different results in each study may be the small number of participants and the absence of surveying exercise experience.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…13 Previous studies based on this phenomenon reported that soccer players showed significantly higher BMD than swimmers who had no weight bearing, but there was no difference between swimmers and weightlifters after the analysis of BMD in soccer players, swimmers, and weight lifters. 11 These results are not consistent as one study showed higher bone density in weight lifters than runners, 19 while another study reported that weight lifters showed significantly higher bone density than non-athletes. 20 In summary, athletes show higher bone density than non-athletes, and it is assumed that the reason for the different results in each study may be the small number of participants and the absence of surveying exercise experience.…”
Section: Discussioncontrasting
confidence: 52%
“…In that study, soccer players were found to have the highest level of bone density. 11 Also, another study reported that long-term resistance exercise was associated with significantly higher bone density. 12 The American College of Sports Medicine (ACSM) also recommends strength or impact exercises such.…”
mentioning
confidence: 99%
“…Pereira Silva et al (2004) investigated the BMD of professional scuba divers and observed there was a significantly lower BMD in divers (p < .05) in both their spine (-3.53%) and hip (-4.80%) compared with age and gender-matched controls. Bellew and Gehrig (2006) investigated female recreational swimmers and reported they had a significantly (p < .001) lower BMD than controls and soccer athletes (p = .001). Similarly, Taaffe et al (1995) investigated the BMD in female gymnasts, swimmers and age and gender-matched controls.…”
mentioning
confidence: 99%
“…A study by Bellew et al (20) compared the BMD of adolescent female soccer players, weightlifters, and swimmers between the ages of 10 and 17 years with the World Health Organization's normative BMD values for adult females. Results revealed that, compared to normative data from the WHO group, the soccer group was the only sport with BMD significantly greater than the norm, while those of the swimmers were significantly less than the norm (P < 0.001), and the weight-lifters were not different from the norm, although in Bellew's study the results of adolescents were compared with those of adults and not an age appropriate control group.…”
Section: Discussionmentioning
confidence: 99%
“…Other research shows that part of the type of physical activity necessary to build and maintain bone density must be weight bearing and that activities with a higher magnitude of skeletal loading and repetitive impact will in turn result in a greater BMD (20). Some authors would even argue that even high muscle forces may not be able to compensate for a lack of impact loading, as studies on competitive cyclists have shown these athletes to have low BMD even though they train intensively (21).…”
Section: Discussionmentioning
confidence: 99%